Islamic Value-Based Conflict Management in Pesantren: Strengthening Dormitory Culture and Multicultural Character Formation - Fadlilah Fadlilah; Fransisko Chaniago; Sizka Farwati; Suci Fitriani; Rizky Takriyanti (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2026)
Life within the Pesantren environment, which brings together students from diverse social, cultural, and educational backgrounds, often generates dynamics and potential conflicts that require effective management. This study analyzes the application of Islamic values-based conflict management in Islamic boarding schools, focusing on strengthening dormitory culture and developing multicultural character. The study employed a qualitative descriptive method, collecting data through observation, in-depth interviews, and documentation. The study was conducted at the Pesantren PKP Al-Hidayah, one of the Pesantren in Jambi, Indonesia. The research results show that dormitory culture is built through a planned and ongoing habituation process, including congregational worship activities, studying, practicing Arabic and English, and participating in social and extracurricular activities. Conflicts between students arise in intrapersonal, interpersonal, intragroup, and intergroup forms, caused by differences in personality, academic and language abilities, rule violations, external factors, and social and cultural diversity. Conflict management is implemented through a tiered, collaborative model that encompasses planning, implementation, and evaluation. This system emphasizes educational guidance, deliberation, and a restorative approach rather than punishment. Evaluation is conducted through documentation and coordination between caregivers, Orsada, and parents to ensure continuous improvement and alignment with the Pesantren’s educational mission. These findings provide practical implications for Pesantren in developing effective dormitory management by integrating Islamic values into daily practices, as well as contributing theoretically to understanding Pesantren as social laboratories for value-based education and conflict transformation.